Vitamin D and athletic performance: the potential role of muscle - Hamilton, B. (Asian Journal of Sports Medicine, 2011)
Vitamin D deficiency is a worldwide epidemic, with well known impacts on calcium metabolism and bone health, but increasingly recognized associations with chronic health problems such as bowel and colonic cancer, arthritis, diabetes and cardiovascular disease. In recent years in the Sports Medicine literature, there has been an increased focus on the potential impact that inadequate Vitamin D levels may have on athletic performance.